Fundamentals of Weather and Climate - McIlveen, Robin (New York Oxford University Press, 2010)
Fundamentals of Weather and Climate offers an engaging and insightful treatment of the behaviour of the lower atmosphere, and takes a quantitative approach to describing the mechanisms underlying this behaviour.
Include Index, Glossary and Bibliography
Keywords: Meteorology -- Atmospheric physics -- Weather